Developmental expression of DAX1 in the European sea bass, Dicentrarchus labrax: lack of evidence for sexual dimorphism during sex differentiation - Power Deborah M; Mylonas Constantinos C; Deloffre Laurence AM; Martins Rute ST; Canário Adelino VM (BMC, 2007)
Abstract Background DAX1 (NR0B1), a member of the nuclear receptors super family, has been shown to be involved in the genetic sex determination and in gonadal differentiation in several vertebrate species. In the aquaculture fish European sea bass, Dicentrarchus labrax, and in the generality of fish species, the mechanisms of sex determination and differentiation have not been elucidated. The present study aimed at characterizing the European DAX1 gene and its developmental expression at the mRNA level. Methods A full length European sea bass DAX1 cDNA (sbDAX1) was isolated by screening a testis cDNA library. The structure of the DAX1 gene was determined by PCR and Southern blot. Multisequence alignments and phylogenetic analysis were used to compare the translated sbDAX1 product to that of other vertebrates. sbDAX1 expression was analysed by Northern blot and relative RT-PCR in adult tissues. Developmental expression of mRNA levels was analysed in groups of larvae grown either at 15°C or 20°C (masculinising temperature) during the first 60 days, or two groups of fish selected for fast (mostly females) and slow growth. Results The sbDAX1 is expressed as a single transcript in testis and ovary encoding a predicted protein of 301 amino acids. A polyglutamine stretch of variable length in different DAX1 proteins is present in the DNA binding domain. The sbDAX1 gene is composed of two exons, separated by a single 283 bp intron with conserved splice sites in same region of the ligand binding domain as other DAX1 genes. sbDAX1 mRNA is not restricted to the brain-pituitary-gonadal axis and is also detected in the gut, heart, gills, muscle and kidney. sbDAX1 mRNA was detected as early as 4 days post hatching (dph) and expression was not affected by incubation temperature. Throughout gonadal sex differentiation (60-300 dph) no dimorphic pattern of expression was observed. Conclusion The sbDAX1 gene and putative protein coding region is highly conserved and has a wide pattern of tissue expression. Although gene expression data suggests sbDAX1 to be important for the development and differentiation of the gonads, it is apparently not sex specific.